PENGARUH DOSIS PUPUK KANDANG SAPI DAN KONSENTRASI PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL KACANG PANJANG (VIGNA SINENIS L.): Pupuk Kandang Sapi, BiotoGrow, Kacang Panjang - karyodikromo, Avi sukma; Sumarmi, Sumarmi; Triyono, Kharis (innofarm, 2024)
Cow manure is useful as a source of humus, as a source of macro and micro nutrients, as a carrier for beneficial microorganisms and also as a growth promoter. The aim of this research was to determine the dosage of cow manure and the concentration of BiotoGrow biofertilizer on growth and yield of long bean (Vigna sinensis L.) and to determine the best dose that can prodive the best results for the growth and yield of long bean variety Kanton Tavi. The method used in the research was a Complete Randomized Block Design (CRBD) with 2 treatment factors and 3 replications. The first factor is giving of a dose of cow manure consisting of 4 levels, namely : S0 = without cow manure, S1 = 1,08 kg/petak , S2 = 1,62 kg/petak, S3 = 2,16 kg/petak the second factor is giving concentration BiotoGrow biofertilizer consists of 4 levels, namely: B0 = without BiotoGrow, B1 = 1,5 ml/liter, B2 = 3 ml/liter , B3 = 4,5 ml/liter. The research shows the interaction og giving a dose of cow manure of 2,16 kg/plot and a BiotoGrow concentration of 4,5 ml/liter on the parameters of fruit number 23,77, fruit length 60,52 cm, fruit weight 21,12 grams, fruit weight per plot 248,93 grams, wet stover weight 471,00 grams and dry stover weight 142,07 grams.